Amorphous Catalysts and Electrochemical Water Splitting: An Untold Story of Harmony. Issue 2 (11th December 2019) - Anantharaj, Sengeni; Noda, Suguru
Abstract: In the near future, sustainable energy conversion and storage will largely depend on the electrochemical splitting of water into hydrogen and oxygen. Perceiving this, countless research works focussing on the fundamentals of electrocatalysis of water splitting and on performance improvements are being reported everyday around the globe. Electrocatalysts of high activity, selectivity, and stability are anticipated as they directly determine energy‐ and cost efficiency of water electrolyzers. Amorphous electrocatalysts with several advantages over crystalline counterparts are found to perform better in electrocatalytic water splitting. There are plenty of studies witnessing performance enhancements in electrocatalysis of water splitting while employing amorphous materials as catalysts. The harmony between the flexibility of amorphous electrocatalysts and electrocatalysis of water splitting (both the oxygen evolution reaction [OER] and the hydrogen evolution reaction [HER]) is one of the untold and unsummarized stories in the field of electrocatalytic water splitting. This Review is devoted to comprehensively discussing the upsurge of amorphous electrocatalysts in electrochemical water splitting. In addition to that, the basics of electrocatalysis of water splitting are also elaborately introduced and the characteristics of a good electrocatalyst for OER and HER are discussed. Abstract : Amorphous materials due to their structural flexibility do have several advantages when they are used as electrocatalysts for the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER). This Review is devoted to discussing the breakthroughs that occurred in this field comprehensively.